2016
DOI: 10.1093/mnrasl/slw220
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence for entropy and energy excess beyond r500 - An end to ICM preheating?

Abstract: Non-gravitational feedback affects the nature of the intra-cluster medium (ICM). Xray cooling of the ICM and in situ energy feedback from AGN's and SNe as well as preheating of the gas at epochs preceding the formation of clusters are proposed mechanisms for such feedback. While cooling and AGN feedbacks are dominant in cluster cores, the signatures of a preheated ICM are expected to be present even at large radii. To estimate the degree of preheating, with minimum confusion from AGN feedback/cooling, we study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…This paper is a continuation of our recent work Iqbal et al (2017) wherein we showed that pre-heating scenarios are ruled out at more than 3σ statistical level. In this work, we present a detailed study of the excess entropy profiles along with feedback energy profiles and discuss the effect of non-thermal pressure and clumping in our estimates.…”
Section: Introductionsupporting
confidence: 64%
“…This paper is a continuation of our recent work Iqbal et al (2017) wherein we showed that pre-heating scenarios are ruled out at more than 3σ statistical level. In this work, we present a detailed study of the excess entropy profiles along with feedback energy profiles and discuss the effect of non-thermal pressure and clumping in our estimates.…”
Section: Introductionsupporting
confidence: 64%
“…We therefore, incorporate both these factors in our calculations. This paper is a continuation of our recent work Iqbal et al (2017) wherein we showed that pre-heating scenarios are ruled out at more than 3σ statistical level. In this work, we present a detailed study of the excess entropy profiles along with feedback energy profiles and discuss the effect of non-thermal pressure and clumping in our estimates.…”
supporting
confidence: 64%
“…The preheating scenario has been directly challenged recently by the findings of Iqbal et al (2017), which in a study of the outskirts of a large sample of clusters, ruled out evidence for non-gravitational preheating to high significance. Focusing on more evolved clusters, the simulations of Guo & Mathews (2010) show that AGN outbursts of extreme energies (10 62 erg) similar to those seen in RX J1532.9+3021 (Hlavacek-Larrondo et al 2013) and MACS J1931.8-2634 (Ehlert et al 2011) would be capable of destroying more established SCCs in the low-z universe.…”
Section: Introductionmentioning
confidence: 99%